Pengaruh Beberapa Jenis Termitisida dalam Mengendalikan Rayap (Captotermes curvignathus Holmgren) di Laboratorium - Ary Hutama S; Yuswani Pangestiningsih; Lisnawita Lisnawita (Universitas Sumatera Utara, 2015)
The objective of this research was to get an effective termiticides to control termites (C. curvignathus) in the laboratory. The research was conducted at Pest Laboratory, Agricultural Faculty, University of Sumatera Utara, Medan, from April until May 2014. The method used Randomized Complete Design Nonfactorial with seven treatments. The tratments were (control, cassava bark 25g/L water, cassava bark 50g/L water, cassava bark 75g/L water, cassava bark 100g/L water, kerosene and termiticide (active ingredient imidakloprid) and three replications. The results showed that kerosene was more effective to control termite that the others with mortality of 95% followed by imidacloprid termitisida (85%), cassava bark 100g / L (76.67%), whereas cassava bark 75g / L, 50 g / L, 25g / L weren’t effective to control termite with percentage of mortality were 65, 50, 46.67% respectively. Termite's death marked by the existence of body color changed from pale white to blackish brown color and stiff body shape then into wrinkles.Keywords : termiticide, Captotermes curvignathus, mortality